THE EFFECTIVENESS OF BLENDED PROBLEM-BASED LEARNING FOR ENHANCING COGNITIVE AND LEARNING OUTCOMES OF STUDENTS‘ CRITICAL THINKING SKILLS ON REDOX MATERIALS - Khasanah Arohmatul; Woro Sumarni (Jurnal Pengajaran MIPA, 2019)
This study aims to determine the effect of the blended problem based learning on cognitive learning outcomes and critical thinking skills in class X MIPA State Senior Highschool 1  Subah. The research method used was an experimental design with a pretest-posttest control group design. The sampling technique used was the cluster random sampling, with class X MIPA 4 as the experimental class and X MIPA 2 as the control class. The analysis technique used is the average difference test, the effect analysis between variables and the determination of the coefficient of determination. The results of the study were obtained by the average value of cognitive learning outcomes and the average score of critical thinking skills. Analysis of influence between variables resulted in a biserial coefficient of 0.23 for cognitive learning outcomes and 0.25 for critical thinking skills. Calculation of the coefficient of determination shows that the application of blended problem-based learning contributes 5.5% to cognitive learning outcomes and 6.5% to critical thinking skills. The results showed that the average value of the experimental class cognitive learning outcomes was 73.71 while the control class was 69.47. The average score of the experimental class critical thinking skills is 29.65 while the control class is 27.88. Based on the results of the study, it can be concluded that the application of blended problem-based learning affects the cognitive learning outcomes and critical thinking skills of class X MIPA State Senior Highschool 1  Subah on redox material.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh blended problem based learning terhadap hasil belajar kognitif dan keterampilan berpikir kritis siswa kelas X MIPA SMA Negeri 1 Subah. Metode penelitian yang digunakan adalah eksperimen dengan desain penelitian pretest-posttest control group design. Teknik sampling yang digunakan yaitu cluster random sampling, dengan kelas X MIPA 4 sebagai kelas eksperimen dan X MIPA 2 sebagai kelas kontrol. Teknik analisis yang digunakan yaitu uji perbedaan rata-rata, analisis pengaruh antar variabel, dan penentuan koefisien determinasi. Hasil penelitian diperoleh rata-rata nilai hasil belajar kognitif dan rata-rata skor keterampilan berpikir kritis. Analisis pengaruh antar variabel menghasilkan nilai koefisien biserial 0,23 untuk hasil belajar kognitif dan 0,25 untuk keterampilan bepikir kritis. Perhitungan koefisien determinasi menunjukkan penerapan blended problem based learning berkontribusi sebesar 5,5% terhadap hasil belajar kognitif dan 6,5% terhadap keterampilan berpikir kritis. Hasil penelitian menunjukkan rata-rata nilai hasil belajar kognitif kelas eksperimen sebesar 73,71 sedangkan kelas kontrol sebesar 69,47. Rata-rata skor keterampilan berpikir kritis kelas eksperimen sebesar 29,65 sedangkan kelas kontrol sebesar 27,88. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan blended problem basedlearning berpengaruh terhadap hasil belajar kognitif dan keterampilan berpikir kritis siswa kelas X MIPA SMA Negeri 1 Subah pada materi redoks.Keywords: Cognitive learning outcomes, critical thinking skills, blended problem-based learning, redox.